O corpo (des)educado: narrativas sobre sexualidades e as trajetórias de escolarização - QUIRINO, Rafael Contini (2018)
This dissertationis in the line of research entitled Public Policies in Education, Educational Practices and Diversity, of the Graduate Program in Education of the Universidade do Oeste Paulista. The objective of this research was to analyze the perception of non-heterosexualy outh about their sexualities, as well as to verify their experiences during the schooling process in the contextof formal education. The adopted epistemological framework is based on post-structuralism and the qualitative approach wasadopted as a methodological design. The research was conducted with Young people who do not identify with the heteronormative patterns in terms of the expression. of their sexualities. In addition, it was considered that these participants stand out for their social actions related to debates about youth protagonism, sexual diversity and drug prevention in their communities, located in theperipheryof a medium-sizedcity in the interior of the state of São Paulo. The instruments used were semi-structured interviews and reflective interviews. The issuesofthe script wereformulatedfromdiscussionsbroughtbythearea-specificliterature. The focus group was also performed as a technique for data collection, conducted through the use of images that portrayed central analytical categories in the adopted the oretical framework. It was also understood that the images would allow a greater approximation of the life stories of the participants, allowing the evocation of subjects not explored just with the use of interviews. For the analysis of the material was used the technique of contente analysis. Fromtheanalyzes, three analytical categories were identified in the Study: a) Structural homophobia; b) Injury in the school environment; c) A network of affective and social support. The results of the work demonstrate that, before a heteronormative society, any expression. Of desireconsidered deviant can be constantly rejected and invisible with in a meticulous system engendered by social practices and discourses, including the formal environments of education at its diferente levels. The research is made relevant by the importance of the theme for thearea of education, especially at the moment when conservative and fundamentalista discourses gain diferente contours and spaces. In addition, the investigative process made it possible to reflect on the extentto which these "abnormal" subjects can transit in formal education spaces, despite the fact that these spaces are configured as homophobic, violent, oppressive and that produce psychic suffering in subjectsthat are notheteronormativepatterns.